Dysphemism on Haters' Comments in Kim Kardashian's Instagram - Nisa, Ianatun; Laili, Elisa Nurul (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
Language serves as a pivotal tool in communication, facilitating the exchange of information, ideas, and emotions. Dysphemism, the use of offensive language to insult or belittle, is prevalent in online interactions, particularly on social media platforms. This study delves into dysphemism within the context of haters' comments on Kim Kardashian's Instagram account. Drawing from a qualitative research design, the study identifies eight types and nine functions of dysphemism prevalent in these comments. These include the use of taboo terms, profane swearing, comparisons to animals, epithets targeting physical characteristics, and more. Furthermore, dysphemistic emojis are analyzed alongside textual dysphemisms, revealing a nuanced layer of expression. The research underscores the significance of understanding dysphemism in online discourse, shedding light on its forms, meanings, and functions. Suggestions for future research include exploring dysphemism across various social media platforms and conducting more comprehensive analyses to enrich our understanding of this linguistic phenomenon.